PENGARUH SEBELUM DAN SETELAH RESHUFFLE KABINET KERJA JILID 2 TERHADAP ABNORMAL RETURN DAN VOLUME PERDAGANGAN SAHAM PADA SEKTOR AGRIBISNIS YANG TERDAFTAR DI BURSA EFEK INDONESIA - Edward Zubir; Soekiyono Soekiyono (Derivatif : Jurnal Manajemen, 2017)
The aims of this research  is to determine the difference in average abnormal returns obtained by investors before and after the reshuffle of Working Cabinet on the Stock Exchange and to know the difference in average trading volume activity before and after the Reshuffle of Working Cabinet at BEI. This research was conducted at companies that entered in LQ 45. The data used is data of daily closing price, market index (JCI). The observation period in this study used a period of events (incidents) with the incident of July 27, 2016. Data analysis technique is done by paired sample t test.Based on the research results, the availability of 12 companies is selected to be the research sample. The result of data analysis can be concluded there is no difference of abnormal return between before and end of reshuffle of Working Cabinet  from H-10 to H + 10. In period H-5 until H + 5 there is no significant difference. This means that investors are not in school against the Reshuffle of the Working Cabinet , the publication of the meeting of the Occupation Reshuffle of the Working Cabinet . Occurrence of Working Cabinet Reshuffle  can no longer trade volume on trading volume (average trading volume activity) on stock Agribusiness sector companies listed on the Indonesia Stock Exchange. There is no difference in the average trading volume activity between before and after the reshuffle of Working Cabinet  of H-10 to H + 10 and from H-5 to H + 5 there is no significant difference.The Candidate Researcher must continue to adequately meet his needs for an event if it will make a purchase or sale of shares. Purchases or sales need to be done both before and after. More important if investors know the cause and effect of an event and how to anticipate it. Potential investors need to obtain information clearly. Keywords: Cumulative Abnormal Return, Reshuffle Cabine